EXTRACT ETHANOL SEAWEEDS LOWERING LEVEL OF SERUM HMG-CoA REDUCTASE ENZYME OF WISTAR RATS HYPERCHOLESTEROLEMIA - Sri Marhaeni Julyasih, Ketut; Wirawan, I Gede Putu (International Journal of Biosciences and Biotechnology; Vol 1 No 1 (2012))
Hypercholesterolemia or hyperlipidemia has been established as an important risk factor of cardiovasculardisease. Patients with hypercholesterolemia usually require a prolonged treatment; and the newer and morepotent generation of antilipid agents is costly. In Bali there are several types of seaweed that are generallyconsumed by local people and known by local names of Bulung Boni (Caulerpa spp.) and Bulung Sangu(Gracilaria spp.). Effect of Bulung Boni and Bulung Sangu extracts to reduce level of HMG-??CoA reductaseenzyme are still very limited both in extent and depth, and further investigations were considered relevantand needed. This experimental study used completely randomized design, using a total of 24 Wistar ratsdivided into six sample groups of equal size, all fed with a diet high in cholesterol content. The six samplegroups were respectively designated as negative control group, positive control group, and four treatedsample groups, respectively, fed orally with a dose of 20 mg and 60 mg extracts of Bulung Boni per 100g ofbody weight per day, and 20 mg and 60 mg extracts of Bulung Sangu per 100g body weight per day. Eachtreatment was repeated four times. Results showed that rats fed with high-??cholesterol diet and treated withoral Bulung Boni or Bulung Sangu extract at a dose of 20 mg and 60 mg/100 g bw/ day were statisticallysignificantly decrease serum HMG-??CoA reductase enzyme levels (p < 0.05) as compared with those of ratsfed with high cholesterol diet without treatment with Bulung Boni or Bulung Sangu extracts. It implied thatBulung Boni and Bulung Sangu extracts decrease level of HMG-??CoA reductase enzyme by significantlylowering serum HMG-??CoA reductase enzyme levels.
Keywords: Caulerpa spp, Gracilaria spp., enzyme HMG?CoA reductase, hypercholesterolemia